Aerobic oxidation of alcohols with air catalyzed by decacarbonyldimanganese. Issue 22 (29th October 2019) - Meng, Shan-Shui; Lin, Li-Rong; Luo, Xiang; Lv, Hao-Jun; Zhao, Jun-Ling; Chan, Albert S. C.
Abstract : Oxidation of various alcohols using air as the ultimate oxidant was realized by Mn without any co-catalysts and additives. Abstract : The oxidation of alcohols to carbonyl compounds using air as the terminal oxidant is highly desirable. As described in previous reports, the abstraction of α-H of the alcohol is the most important step, and it typically requires not only a metal catalyst but also complex ligands, co-catalysts and bases. Herein, we report a practical and efficient method for the oxidation of primary alcohols, secondary alcohols, 1, 2-diols, 1, 2-amino alcohols, and other α-functionalized alcohols using a commercially available catalyst, Mn2 (CO)10, and no additives. Preliminary mechanistic studies indicated that an alkoxyl radical intermediate existed in our system, and a plausible mechanism consistent with the experimental results and literature was proposed.